C4-monomethylsterol β-glucoside and its synthase in Aurantiochytrium limacinum mh0186. (5th July 2021) - Endo, Ikumi; Watanabe, Takashi; Miyamoto, Tomofumi; Monjusho-Goda, Hatsumi; Ohara, Junichiro; Hayashi, Masahiro; Hama, Yoichiro; Ishibashi, Yohei; Okino, Nozomu; Ito, Makoto
Abstract: Thraustochytrids, unicellular marine protists, synthesize polyunsaturated fatty acids (PUFAs) and PUFA-containing phospholipids; however, little is known about their glycolipids and their associated metabolism. Here, we report two glycolipids (GL-A, B) and their synthases in Aurantiochytrium limacinum mh0186. Two glycolipids were purified from A. limacinum mh0186, and they were determined by gas chromatography, mass spectrometry and 2D nuclear magnetic resonance to be 3-O-β-D-glucopyranosyl-stigmasta-5, 7, 22-triene (GL-A) and 3-O-β-D-glucopyranosyl-4α-methyl-stigmasta-7, 22-diene (GL-B), both of which are sterol β-glucosides (β-SGs); the structure of GL-B has not been reported thus far. Seven candidate genes responsible for the synthesis of these β-SGs were extracted from the draft genome database of A. limacinum using the yeast sterol β-glucosyltransferase (SGT; EC 2.4.1.173) sequence as a query. Expression analysis using Saccharomyces cerevisiae revealed that two gene products (AlSGT-1 and 2) catalyze the transfer of glucose from uridine diphosphate (UDP)-glucose to sterols, generating sterylglucosides (SGs). Compared to AlSGT-1, AlSGT-2 exhibited wide specificity for sterols and used C4-monomethylsterol to synthesize GL-B. The disruption of alsgt-2 but not alsgt-1 in strain mh0186 resulted in a decrease in the total SG and an almost complete loss of GL-B, indicating that AlSGT-2 is responsible for the synthesis of β-SGs in A. limacinum mh0186, especially GL-B, which possesses a unique sterol structure.